2011
DOI: 10.1080/09585192.2011.543629
|View full text |Cite
|
Sign up to set email alerts
|

Strategic alliance team diversity, coordination, and effectiveness

Abstract: Drawing upon literatures on strategic alliances, teams, and diversity, we propose that strategic alliance team diversity warrants further examination. We suggest that strategic alliance team coordination moderates the relationship between strategic alliance team diversity and effectiveness. Specifically, we hypothesize that coordination strengthens the negative relationship between observable diversity characteristics of nationality and gender and team effectiveness. We also argue that coordination strengthens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 84 publications
1
47
0
Order By: Relevance
“…Studies conducted by Bekele and Worku [53] and Zoogah, Vora, Richard and Peng [75] have found that the failure of tertiary level academic institutions to equip young graduates with skills that are relevant to the actual needs of society is the key reason why young graduates in the world's least developed nations are virtually unemployable.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Studies conducted by Bekele and Worku [53] and Zoogah, Vora, Richard and Peng [75] have found that the failure of tertiary level academic institutions to equip young graduates with skills that are relevant to the actual needs of society is the key reason why young graduates in the world's least developed nations are virtually unemployable.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…On the other hand, strategic alliances lead to transactions which ultimately help alliance parties to achieve their goals. Also, this partnership improves their performance by reducing costs, acquiring knowledge and market development (Zoogah et al, 2011).…”
Section: Strategic Alliancementioning
confidence: 99%
“…Cultural diversity may have both positive and negative influences on group performance (Milliken and Martins, 1996;Williams and O'Reilly, 1998;van Knippenberg et al, 2004;Adler, 2003;Zoogah et al, 2011): it can increase productivity (Stahl et al, 2010a), creativity (McLeod et al, 1996), and the quality of decision making (Shachaf, 2008), but may also hinder communication (Adler, 2003), trigger conflict, and decrease social integration (Stahl et al, 2010b). Advantages of cultural diversity can be substantial: in a field study, Ng and Tung (1998) found that culturally diverse organizations have higher organizational effectiveness, in particular with increased profitability.…”
Section: The Moderating Effect Of Group Cultural Diversitymentioning
confidence: 99%